Proteomic Profiling Reveals Roles of Stress Response, Ca2+ Transient Dysregulation, and Novel Signaling Pathways in Alcohol‐Induced Cardiotoxicity. (16th October 2020) - Liu, Rui; Sun, Fangxu; Forghani, Parvin; Armand, Lawrence C.; Rampoldi, Antonio; Li, Dong; Wu, Ronghu; Xu, Chunhui
Abstract : Background: Alcohol use in pregnancy increases the risk of abnormal cardiac development, and excessive alcohol consumption in adults can induce cardiomyopathy, contractile dysfunction, and arrhythmias. Understanding molecular mechanisms underlying alcohol‐induced cardiac toxicity could provide guidance in the development of therapeutic strategies. Methods: We have performed proteomic and bioinformatic analysis to examine protein alterations globally and quantitatively in cardiomyocytes derived from human‐induced pluripotent stem cells (hiPSC‐CMs) treated with ethanol (EtOH). Proteins in both cell lysates and extracellular culture media were systematically quantitated. Results: Treatment with EtOH caused severe detrimental effects on hiPSC‐CMs as indicated by significant cell death and deranged Ca 2+ handling. Treatment of hiPSC‐CMs with EtOH significantly affected proteins responsible for stress response (e.g., GPX1 and HSPs), ion channel‐related proteins (e.g. ATP1A2), myofibril structure proteins (e.g., MYL2/3), and those involved in focal adhesion and extracellular matrix (e.g., ILK and PXN). Proteins involved in the TNF receptor‐associated factor 2 signaling (e.g., CPNE1 and TNIK) were also affected by EtOH treatment. Conclusions: The observed changes in protein expression highlight the involvement of oxidative stress and dysregulation of Ca 2+ handling and contraction while also implicating potential novel targets in alcohol‐induced cardiotoxicity. These findings facilitate further exploration of potential mechanisms, discovery of novel biomarkers, and development of targeted therapeutics against EtOH‐induced cardiotoxicity. Abstract : Treatment of human stem cell‐derived cardiomyocytes with ethanol results in cell death and abnormal Ca 2+ handling. Proteomic profiling and bioinformatic analysis reveal that ethanol treatment affects the expression of proteins involved in oxidative stress, ion channels, myofibril structure, focal adhesion, extracellular matrix and TRAF2 signaling.